2021
DOI: 10.1007/s11166-021-09363-8
|View full text |Cite
|
Sign up to set email alerts
|

Crowded out: Heterogeneity in risk attitudes among poor households in the US

Abstract: Not much is known about the heterogeneity of risk attitudes among poor households in rich countries. This paper provides estimates from a unique data set collected among the urban poor in Atlanta, Georgia. The data set includes lab-in-the-field experiments on the relationship between risk attitudes and several household characteristics. Apart from looking at income, wealth, and education, we are particularly interested in household composition as it captures the number and kind of people who are dependant on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…To win this competition, each individual tries to improve their education and skills with a certain specialization. Furthermore, Physiological Theory doubts this axiom, with evidence that in many countries, such as India, Indonesia, and China, the population density is very high, but population growth is also high (Galliera & Rutström, 2021). Instead, Malthus' assumption is much more concrete, in an area with high fertility rates, population growth is low due to high mortality.…”
Section: Literature Review and Theoreticalmentioning
confidence: 99%
“…To win this competition, each individual tries to improve their education and skills with a certain specialization. Furthermore, Physiological Theory doubts this axiom, with evidence that in many countries, such as India, Indonesia, and China, the population density is very high, but population growth is also high (Galliera & Rutström, 2021). Instead, Malthus' assumption is much more concrete, in an area with high fertility rates, population growth is low due to high mortality.…”
Section: Literature Review and Theoreticalmentioning
confidence: 99%
“…Studying vineyards in Catalonia (Spain), Kallas et al, (2010) found that farmers' objectives influence the decision to convert to organic farming, and that those who are not risk averse are more likely to adopt it. Galliera and Rutström, (2021) highlight perceptions of costs vs. benefits, direct information, know-how, and support for the investments as key factors that promote adoption of BMPs and sustainable pesticide use to improve groundwater quality in hilly vineyards in Italy. In a study of vineyard crop protection in Galicia (Spain), Pereira et al, (2017) explained that the low rate of adoption of agroecological innovations in viticulture was due to their higher prices, higher labor costs, and novelty.…”
Section: Factors That Influence Adoption Of Agroecological Practices ...mentioning
confidence: 99%